Adrian Mole : czas cappuccino - Townsend, Sue.; Umiastowska-Kopec, Barbara (Warszawa : Wydawn. W.A.B., 2002)
Polish translation of "Adrian Mole: the cappucino years". Continues stories of a British teenager's life from his diary entries.
Translation of: Adrian Mole : the cappuccino years.
Keywords: Mole, Adrian (Fictitious character) -- Fiction; Single fathers -- Fiction; Young men -- Fiction; England -- Fiction